2015
DOI: 10.1371/journal.ppat.1005012
|View full text |Cite
|
Sign up to set email alerts
|

TRIM30α Is a Negative-Feedback Regulator of the Intracellular DNA and DNA Virus-Triggered Response by Targeting STING

Abstract: Uncontrolled immune responses to intracellular DNA have been shown to induce autoimmune diseases. Homeostasis regulation of immune responses to cytosolic DNA is critical for limiting the risk of autoimmunity and survival of the host. Here, we report that the E3 ubiquitin ligase tripartite motif protein 30α (TRIM30α) was induced by herpes simplex virus type 1 (HSV-1) infection in dendritic cells (DCs). Knockdown or genetic ablation of TRIM30α augmented the type I IFNs and interleukin-6 response to intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 32 publications
1
135
0
Order By: Relevance
“…Furthermore, it was reported that STING can also undergo lysosomal degradation (38). To test whether proteasomal degradation may be involved in the decrease of STING levels after stimulation of BMDCs with c‐di‐AMP or cGAMP, we conducted experiments in the presence of MG132, which is used as an inhibitor of proteasome activity (32, 36). Although MG132 could attenuate CDN‐dependent degradation of STING, involvement of the proteasome could not be confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was reported that STING can also undergo lysosomal degradation (38). To test whether proteasomal degradation may be involved in the decrease of STING levels after stimulation of BMDCs with c‐di‐AMP or cGAMP, we conducted experiments in the presence of MG132, which is used as an inhibitor of proteasome activity (32, 36). Although MG132 could attenuate CDN‐dependent degradation of STING, involvement of the proteasome could not be confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…The autophagy‐associated kinase ULK1 is indirectly activated by STING signaling and phosphorylates STING after it traffics to the Golgi to promote its degradation . EIF3S5, TRIM29, TRIM30α, and RNF5 also target STING for degradation by K48‐linked ubiquitination . RNF26 blocks RNF5 ubiquitination by adding a K11‐linked ubiquitin .…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
“…Phosphorylated on Ser366 by TBK1, STING interacts with and activates IRF3, thus inducing IFNβ upregulation; STING also drives NF-κB phosphorylation, nuclear translocation, and target gene expression [33]. As a negative regulatory feedback mechanism to prevent the overstimulation of innate immune genes, E3 ligases are responsible for ubiquitin-dependent STING degradation in viral infections [34, 35]. …”
Section: Cytosolic Nucleic Acid Sensing Pathwaysmentioning
confidence: 99%